2019
DOI: 10.1155/2019/7848314
|View full text |Cite
|
Sign up to set email alerts
|

The HLA-Cw12 Allele Is an Important Susceptibility Allele for Psoriasis and Is Associated with Resistant Psoriasis in the Turkish Population

Abstract: Background. Psoriasis is a multifactorial immune-mediated inflammatory disease triggered by both genetic and environmental factors. The strong association between psoriasis and HLA-C⁎06 allele has been demonstrated in various races. The HLA-C⁎12 allele is closely related to the HLA-C⁎06 family of alleles and shares identical sequences. To the best of our knowledge, there is no information about the relationship between HLA-C⁎12 and psoriasis in the Turkish population. The present study aims to determine this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…A summary of characteristics of patients with psoriasis carrying HLA-Cw1 in comparison to HLA-Cw6 is provided in Table 2. HLA-Cw6 is the most well-recognized HLA serotype, affecting susceptibility, phenotype, disease Ethnicities Kuwait [15] All ethnicities (higher in Caucasians) Pakistan [16] Singapore Chinese [17] Southern Chinese [11] Thai [12] Turkish [14] Phenotypes…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A summary of characteristics of patients with psoriasis carrying HLA-Cw1 in comparison to HLA-Cw6 is provided in Table 2. HLA-Cw6 is the most well-recognized HLA serotype, affecting susceptibility, phenotype, disease Ethnicities Kuwait [15] All ethnicities (higher in Caucasians) Pakistan [16] Singapore Chinese [17] Southern Chinese [11] Thai [12] Turkish [14] Phenotypes…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the HLA-C*01 allele was significantly more frequent in Turkish patients with psoriasis than in control groups (8.1% vs 2.1%, p = 0.02), leading to an OR of 4.15 (95% confidence interval [CI] 1.15-15.01) [14]. In one study that recruited Kuwait children, the association of HLA-Cw1 with psoriasis was observed in 9 out of 50, resulting in an OR of 3.01 (95% CI 1.00-9.50) [15].…”
Section: Hla-cw1 Allele Frequency In Patients With Psoriasismentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we found that both HLA-A28(68) and Cw12 were also associated with ASAS − but not with PsA or uSpA, suggesting that these alleles can confer susceptibility to ASAS − . While HLA-A28, with its splits 68 and 69, has been demonstrated to be significantly associated with B27 risk-related diseases, including AS [ 23 ], reactive arthritis [ 23 ], juvenile chronic polyarthropathy [ 23 ], and intermediate uveitis [ 24 ], only a minimal predisposition to cutaneous psoriasis has been reported for HLA-Cw12 [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Описаны генетические маркеры, позволяющие прогнозировать характер течения заболевания или развития определенной клинической формы. Например, при обнаружении аллеля HLA-C*12 и полиморфного варианта Pro гена p53 (регулирует клеточный цикл) повышена вероятность тяжелого течения псориаза [19,20].…”
Section: прогностические бмunclassified